ANALISIS PEMANFAATAN ENSIKLOPEDIA DI PERPUSTAKAAN IAIN TULUNGAGUNG - Binti Nuryanti; Eka Era Artika; Novita Wulandari; Nafisa Asma Nurul Aulia (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
The library as an information resource is a reference for the advancement of an institution, especially educational institutions. One type of library is the college library. The library provides a variety of services to meet the information needs of users, for example reference services that provide various collections which are collections of general reference sources. The library provides various collections in the form of books or digital collections, one of the publications in the library is the encyclopedia. Encyclopedias contain various kinds of objects accompanied by information and comprehensive and complete information relating to the objects discussed in the object discussed in the encyclopedia are objects or material from various things of science. Utilization of an encyclopedia for the academic community has an important role. This study is about the use of encyclopedias in the Tulungagung IAIN Library using a qualitative descriptive approach to research methods by means of interviews with informants that are thoroughly described. The qualitative descriptive approach method is a method of processing data by analyzing factors related to the object of research by presenting data more deeply to the object of research. Based on this study the use of encyclopedias in the Tulungagung IAIN library is still rarely used by users. This can occur because the lack of user knowledge of the benefits of the encyclopedia to improve reference services needs to be developed through promotion.